Acute stroke care practice among emergency and medicine staff in Qassim region, Saudi Arabia - Alqwaifly, Mohammed (International Journal of Advances in Medicine, 2020)
Background: Stroke is a major cause of morbidity and disability worldwide. However, its outcomes have improved in the last few years with advancement in acute stroke treatment, including the use of tissue plasminogen activator (t-PA) within 4.5 hours of onset, which led several international guidelines to adopt it as the standard of care. In this study, authors sought to assess the knowledge, practices, and attitudes of emergency and medicine staff in Qassim, Saudi Arabia toward acute ischemic stroke care. Methods: A quantitative observational cross-sectional study involving 148 physicians from emergency and medicine departments (only three neurologists) was conducted in three main hospitals of the Qassim region, Saudi Arabia. Information was obtained from a self-administered questionnaire. A logistic regression model was used to control for potential confounding factors. Results: Ninety-two percent of participants were aware of t-PA. Eighty-seven percent of participants thought that t-PA was an effective treatment for acute ischemic stroke. Only 20% of participants had given t-PA or participated in the use of t-PA in acute ischemic stroke. Moreover, 64% of participants believed that allowing blood pressure to remain high was the most appropriate action in the first 24 hours in acute ischemic stroke patients who presented outside the t-PA window. Conclusion: Most of the emergency and medicine staff are well informed about t-PA, but the majority of these physicians have never given t-PA or participated in the administration of t-PA to a stroke patient. The main finding here is the positive outlook among emergency and medicine physicians in Qassim toward training in acute stroke care and administering t-PA for stroke, which will positively impact patient outcomes.